Analysis of Content and Organization of Software Engineer Training at the Universities of the USA - Vladyslav Kruhlyk; Viacheslav Osadchyi; Svitlana Symonenko (Pedagogical Discourse, 2016)
The paper deals with the problems of software engineer training at the advanced universities of the USA. Modern statistical data proving the popularity and high demand for a software engineer (a software developer) profession in the world are presented. Some ranking data related to countries of the world and numbers of best universities providing the best IT-education are demonstrated. It is focused that there are 63 universities from the USA in the Academic Ranking of World Universities in Computer Science – 2015 (Shanghai Ranking). It is noted that in the USA educational establishments offer different degrees: Associate’s Degree in Software Engineering, Bachelor’s Degree in Software Engineering, Master’s Degree in Software Engineering and PhD in Software Engineering. Curriculum Guidelines for Undergraduate Degree Programs in Software Engineering developed by international organisations (Association for Computing Machinery (ACM) and IEEE Computer Society (IEEE CS), their content and peculiarities are analysed. It is shown that in university curricula much attention should be given not only to technical and professional knowledge, but to interpersonal relations, communication and problem-solving skills. Software engineering curricula of leading American universities (Rochester Institute of Technology and José State University) are compared. Similar aspects in software engineering curricula of these universities are highlighted. It was shown that professional training, liberal arts and sciences, natural sciences, wellness education and language knowledge are important for software engineers. It is emphasized that it is necessary to study, adapt and implement the positive experience of software engineer training of American universities to Ukrainian higher educational establishments.Key words: professional training, software engineering, curriculum, software engineer, software engineering education knowledge (SEEK).